Geographic Distribution of Secondary Metabolite Genes in the Marine Actinomycete Salinispora arenicola - Edlund, Anna (American Society for Microbiology, 2011)
The molecular fingerprinting technique terminal-restriction fragment length polymorphism (T-RFLP) was used in combination with sequence-based approaches to evaluate the geographic distribution of secondary metabolite biosynthetic genes in strains of the marine actinomycete Salinispora arenicola. This study targeted ketosynthase (KS) domains from type I polyketide synthase (PKS) genes and revealed four distinct clusters, the largest of which was comprised of strains from all six global locations sampled. The remaining strains fell into three smaller clusters comprised of strains derived entirely from the Red Sea, the Sea of Cortez, or around the Island of Guam. These results reveal variation in the secondary metabolite gene collectives maintained by strains that are largely clonal at the 16S rRNA level. The location specificities of the three smaller clusters provide evidence that collections of secondary metabolite genes in subpopulations of S. arenicola are endemic to these locations. Cloned KS sequences support the maintenance of distinct sets of biosynthetic genes in the strains associated with each cluster and include four that had not previously been detected in S. arenicola. Two of these new sequences were observed only in strains derived from Guam or the Sea of Cortez. Transcriptional analysis of one of the new KS sequences in conjunction with the production of the polyketide arenicolide A supports a link between this sequence and the associated biosynthetic pathway. From the perspective of natural product discovery, these results suggest that screening populations from distant locations can enhance the discovery of new natural products and provides further support for the use of molecular fingerprinting techniques, such as T-RFLP, to rapidly identify strains that possess distinct sets of biosynthetic genes.